THE CORRELATION OF INCONSISTENCY URINE TO DEPRESSION ON ELDERLY IN WREDHA DHARMA BHAKTI NURSING HOME OF PAJANG SURAKARTA - Wisti .; Widiyono .; Atik Aryani (Jurnal Ilmu Keperawatan Indonesia (JIKI), 2019)
Background: Inconsistency urine is one of the elderly problems that requires appropriate treatment. Elderly with inconsistency urine often get depression.It is due to they feel alone and despicable about their condition. The results of interviews with 10 respondents indicated that where 6 elderly who experienced inconsistency urineand frequent urination even wet their bed.Whereas, 4 people who the depressed since they feel despicable for their condition. Objective: To determine the correlation of inconsistency urine to depression in elderly atWredha Dharma Bhakti nursing home Pajang Surakarta. Method: This research belongs to descriptive correlational with a cross-sectional approach. The population is 86 elderly at the Wredha Dharma Bhakti nursing home Pajang Surakarta. The sampling technique used purposive sampling with a total sample of 65 respondens. The instrument variables for inconsistency urineused the Sandvix Severity Index (SSI) by Miller (2009).Whereas, the depression instruments variable in elderly used a Geriatric Depression Scale (GDS) questionnaire by Brink and Yesavage (1982). Data analysis techniques used Chi Square. Results: (1) Almost of elderly in Wredha Dharma Bhakti nursing home Pajang Surakarta have inconsistency urine acute with 27 people (41.54%). (2) Almost of elderly in Wredha Dharma Bhakti nursing home Pajang Surakarta get depression in the mild category with 23 elderly (35.38%). (3) There is a significant correlation inconsistency urine to depression in elderly in Wredha Dharma Bhakti nursing home Pajang Surakarta, with a chi square correlation coefficient of 47,150; significance of 0,001 and CI of 0,648. Conclusion: There is a significant correlation inconsistency urine to depression in elderly in Wredha Dharma Bhakti nursing home Pajang Surakarta